KOMODIFIKASI GAYA HIDUP TRAVELING DALAM KONTEN INSTAGRAM @BACKPACKERTAMPAN DAN @AHMADRIFYANNUR DI KALANGAN GENERASI Z - Abdul Hadi Almaghribi; Adam Reynaldi Sofyan; Rifma Ghulam Dzaljad (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
This study discusses the traveling lifestyle among Generation Z from the perspective of the Frankfurt School of Critical Theory. The growing phenomenon of traveling through digital media is no longer understood only as an activity to satisfy oneself by going to dream places or simply to relieve stress (use value), but also becomes a popular cultural lifestyle that can generate exchange value, such as becoming a commodity to generate profits through promotional content for open trip services and endorsements. In the perspective of the Frankfurt School of Critical Theory, this condition shows how social media forms the commodification of the traveling lifestyle into a commodity that is traded in the market, based on the Political Economy of Communication Theory - Vincent Mosco. This study uses a qualitative approach with digital observation techniques on the Instagram social media platform, as well as a documentation study of the content of the @backpackertampan and @ahmadrifyannur accounts with a travel theme. The results of the study indicate a relationship between social media, the cultural industry, and digital capitalism in shaping the traveling lifestyle among Generation Z.